Rage against the machine: A money-burning field experiment - Muhammad Ryan Sanjaya (Universitas Islam Indonesia, 2022)
Purpose ― This study investigates antisocial behaviour where participants made payoff destruction decisions (“money burning”) that are conditional on the co-participant being a human or a computer. Methods ― This study uses the joy-of-destruction minigame experiment with Indonesian citizens living in Australia as the participants. Regression methods are used to observe whether discrimination occurs and to identify factors associated with antisocial behaviour. Findings ― This study finds money burning against the computer to be more prevalent than against humans. There was very limited support that such behaviour was correlated with demographic characteristics or subjective norms, suggesting that the presence of a computer co-participant drives the result. Implications ― The results have a methodological implication for experimental economics where experimenters should anticipate that computer players may have an unforeseen impact on human behaviour. Policy-wise, the study shows a relatively cohesive community which may be driven by the multicultural policy of Australia. Originality ― This is the first antisocial behaviour economics experiment that includes a computer as a potential co-participant.